Production of interspecies cloned caprine embryos and mouse embryonic fibroblast feeder cell layer to culture embryonic stem cell / Nurin Farhanah Norzaiwin - Nurin Farhanah , Norzaiwin (2017)
The extreme variability in efficiency of the interspecies somatic cell nuclear transfer showed improvement is needed to both procedures and resources used to produce interspecies cloned caprine embryos blastocysts prior subjected for production of embryonic stem cell on mouse embryonic fibroblast feeder cell layer. The main objective of this study was to produce interspecies cloned caprine embryos and mouse embryonic feeder cell layer which was important for production of embryonic stem cell outgrowth. Briefly, caprine ear fibroblast cells of Boer and Katjang goats were cultured and cryopreserved as donor karyoplasts (Experiment 1). For recipient cytoplasts, bovine cumulus oocytes complexes were collected from abattoir-derived ovaries and subjected for in vitro maturation duration: a) 22-24 hours or b) 25-27 hours before subjected to interspecies somatic cell nuclear transfer using the caprine ear fibroblast karyoplasts. The embryos in vitro development was recorded (Experiment 2). The post-activated couplets and 8-cells were treated with trichostatin A (25 nM) before culturing. The morula and blastocyst rates of the treated embryos were recorded (Experiment 3). Blastocysts produced in Experiment 3 were used for whole blastocyst culture on mouse embryonic feeder cell layer in attempt to produce embryonic stem cell. The mouse embryonic fibroblasts were cultured from murine foetal ages of 14 and 15 days post coitus and cryopreserved using quick freezing technique (Experiment 4). In Experiment 1, generally, no significant effects of breed and gender were observed on viability rate of fresh early passages of the ear fibroblast culture. No significant different between the crypreserved and fresh passages. Based on the similar morphological characteristics and comparable viability rate of the ear fibroblast cell, suggesting stable production of ear fibroblast cell line could be produced using adult female and male Boer and Katjang up to three passages. In Experiment 2, combination 22-24 hour maturation duration of bovine cytoplasts and Boer and Katjang male ear fibroblast karyoplasts gave significantly better (P<0.05) 2-cell and 4-cell rates (84.17% with 73.14% and 61.25% with 64.99%, respectively). Only combination of 22-24 hours maturation cytoplast with both female and male Boer ear fibroblast karyoplast successfully produced interspecies cloned caprine blastocyst (0.49% and 1.50%, respectively). In Experiment 3, no significant difference of morula and blastocyst rate of interspecies cloned caprine embryos regardless it was treated at post-activated couplets or 8-cell as well as non-treated cloned embryos. In Experiment 4, no significant difference on viability rate was observed between the 14 and 15 days post coitum. Meanwhile, the frozen-thawed passages of the mouse embryonic fibroblast cell cultures were significantly lower (P<0.05) compared with fresh passages between foetal ages. The current study also attempted to culture embryonic stem cell outgrowth on the mouse embryonic fibroblast feeder cell layer, however, no successful attachment of inner cell mass was observed. In conclusion, the current study elucidated several selected issues on the donor karyoplast, recipient cytoplast quality and also treatment of histone deacetylase inhibitor in in vitro culture of interspecies cloned caprine embryos. Interspecies somatic cell nuclear transfer in caprine is an alternative to the intraspecies, however, further optimisation on protocol is needed prior to be routinely used.